Vantagens comparativas reveladas das exportações da Argentina, Brasil, Chile e México (1996-2006): reprimarização ou diversificação? - Silva, Andrea dos Santos (2008)
The main objective of this paper is to answer the question: in the period 1996-2006, the Argentina, Brazil, Chile and Mexico export pattern was reprimarizated or diversified? The answer search is centralized in the index of revealed comparative advantage calculus and in the export classification according to its technological contents. Those four countries had adopted different strategies in order to face, in the last years, politicaleconomic crises, internals and externals, and the impact concerning, in a way, a growing international primary products demand, specially the Chinese, and, in the other way, a growing competition cheap-labor intensive, but with some technology incorporated Asian products export. Although, those Latin-Americans countries have their export pattern with varied characteristics, their economies have been showing record export volume. This paper let to conclude that the empirical evidences do not corroborate the reprimarization hypothesis. The countries, in 2006, were manufactures exporters. Argentina, Brazil and Chile had a specialized low and/or middle-low technology manufactures export pattern and Mexico, however, have been exported higher-level technology products